RANCANG BANGUN PROTOTYPE PEMBANGKIT LISTRIK TENAGA SURYA UNTUK SISTEM PENERANGAN RUMAH - Lili Ruhyana Ruhyana Lie; Fikri Ulul Albab; Gelar Prachasti Ramdhani (Jurnal Fakultas Teknik Kuningan, 2022)
In life, in nature there is potential energy that can be utilized for human life behind the ineffectiveness of fossil energy for the environment, the use of natural resources that can be renewed by utilizing the energy contained in the heat of the sun. Utilization of solar thermal energy can be converted into useful power by using solar power plants (PLTS), therefore solar power plants are very potential to be developed in Indonesia, because Indonesia's climate is suitable as a tropical country with sunshine throughout the year. Solar Power Generation (PLTS) is a relatively new method of generating electrical energy by utilizing solar energy. The Solar Power Generation System (PLTS) as a power plant is directed so that it can be utilized by users who are not reached by PLN. The author conducted a study which was conducted to find out how potential solar thermal energy is to be used as a solar power plant, the use of natural resources is carried out in order to find out how potential the use of PLTS is. The process of generating solar power can be done with sunlight in order to produce electrical energy and be used for home lighting systems. One unit of lighting with 10 Watt specifications requires 132Wh. In solar panels there will be power loss depending on the type and quality of the solar panels, to stabilize the need for electricity consumption to be no less than the safe requirement, the total power per day is multiplied by 0.13 = 13%. This value must be generated by the solar panel